Penerapan Teori Humanistik Dalam Mengoptimalkan Gaya Belajar Siswa Di Kelas 8B MTSN 1 Sinjai - Suriyati Suriyati; Rahmatullah Rahmatullah; Jamaluddin Jamaluddin; Mustamir Mustamir; Mustaina Mustaina; Mayangiani Mayangiani (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2025)
This study aims to describe the application of humanistic theory in optimizing student learning styles at MTsN 1 Sinjai. The method used in this study is descriptive, with data collection techniques including in-depth interviews and documentation of teachers and students. The results of this study indicate that the application of a humanistic theory approach can optimize learning motivation, self-confidence, active participation, and the effectiveness of diverse student learning styles, such as visual, auditory, and kinesthetic. Teachers act as facilitators who understand students' emotional needs and learning styles. Problem-based learning strategies and hands-on practices such as public speaking have been proven to create a comfortable and supportive learning atmosphere. However, challenges such as gadget misuse are obstacles that need to be managed through collaboration between teachers and parents. A supportive learning environment, freedom of self-expression, and recognition of diverse learning styles are key factors in the successful implementation of this approach. Therefore, the application of humanistic theory is recommended as an alternative approach in creating humanistic, adaptive, and meaningful learning in the school environment.